The Developing Human Connectome Project Neonatal Data Release - Edwards, A. David; Rueckert, Daniel; Smith, Stephen M.; Abo Seada, Samy; Alansary, Amir; Almalbis, Jennifer; Allsop, Joanna; Andersson, Jesper; Arichi, Tomoki; Arulkumaran, Sophie; Bastiani, Matteo; Batalle, Dafnis; et al. (Frontiers in Neuroscience, 2022)
The Developing Human Connectome Project has created a large open science resource which provides researchers with data for investigating typical and atypical brain development across the perinatal period. It has collected 1228 multimodal magnetic resonance images of fetal and/or neonatal brain from 1173 participants, together with collateral demographic, clinical, family, neurocognitive and genomic data. All subjects were studied in utero and/or soon after birth on a single MRI scanner using specially developed scanning sequences which included novel motion-tolerant imaging methods. Imaging data are complemented by rich demographic, clinical, neurodevelopmental, clinical, and genomic information. The project is now releasing a large set of neonatal data; fetal data will be described and released separately. This release includes scans from 783 infants of whom: 583 were healthy infants born at term; as well as preterm infants; and infants at high risk of atypical neurocognitive development. Many infants were imaged more than once to provide longitudinal data, and the total number of datasets being released is 887. We now describe the dHCP image acquisition and processing protocols, summarize the available imaging and collateral data, and provide information on how the data can be accessed.